CHANGES IN THE OCULAR MICROCIRCULATION AFTER VITREORETINAL SURGERIES FOR INTRAOCULAR HEMORRHAGE - V. V. DASHINA; A. V. MALYSHEV; S. V. YANCHENKO; O. I. LYSENKO; I. V. GRISHCHENKO; A. N. SERGIYENKO (Кубанский научный медицинский вестник, 2017)
Aim. To explore ocular microcirculation in patients with intraocular hemorrhage.Material and Methods. Microcirculation was investigated in 26 patients after subtotal posterior vitrectomy with the use of a laser blood analyzer LAK-01 and a computer program to carry out spectral analysis of the signal. Statistical processing of the results was performed using AnalystSoft software package, BioStat 2007.Results of the study. Ocular microcirculation in the control group was characterized by high levels of blood perfusion and metabolic activity, symmetrical distribution of arterial inflow and venous outflow. Evaluation of microcirculation parameters in patients with intraocular hemorrhage demonstrated a significant fall of these figures.Conclusion. Surgical removal of intraocular hemorrhage leads to a signficant improvement of ocular microcirculation.